The Influence of CPR (Cardiopulmonary Resuscitation) Educational Videos On The Level Of Knowledge of 5Th Semester Undergraduate Nursing Students The Muhammadiyah Health Institute of West Kalimantan - Kerol Myle Punjanan; Annisa Rahmawati; Wien Fitrian Roshandri; Haryanto Haryanto; Ditha Astuti Purnamawati (Journal of Innovative and Creativity (Joecy), 2026)
Background: Cardiac arrest is a life-threatening emergency condition that can lead to death if not managed promptly. One of the most essential initial interventions in cardiac arrest management is Cardiopulmonary Resuscitation (CPR). Nursing students, as future healthcare providers, are expected to have adequate knowledge of CPR to perform effective first aid. Educational videos are considered one of the learning methods that can enhance students’ knowledge. Objective: This study aimed to determine the effect of CPR educational videos on the knowledge level of fifth-semester undergraduate nursing students at ITEKES Muhammadiyah West Kalimantan. Methods: This research employed a quantitative method with a pre-experimental one group pretest–posttest design. The sample consisted of fifth-semester nursing students selected using a total sampling technique totaling 107 people. Data were collected using a CPR knowledge questionnaire administered before and after the educational video intervention. Data analysis was conducted using the Wilcoxon Signed Rank Test to examine differences in knowledge levels before and after the intervention. Research Result: Showed an improvement in students’ knowledge levels after receiving the CPR educational video. The educational video was proven to be an effective learning medium in enhancing students’ understanding of CPR. Therefore, CPR educational videos can be utilized as an alternative learning method in nursing education to improve students’ readiness in managing emergency situations, particularly cardiac arrest.